The Role of Peroxisome Proliferator-Activated Receptors and Their Transcriptional Coactivators Gene Variations in Human Trainability: A Systematic Review - Petr, Miroslav; Stastny, Petr; Zajac, Adam; Tufano, James J; Maciejewska-Skrendo, Agnieszka (International journal of molecular sciences, 2018)
BACKGROUND: The peroxisome proliferator-activated receptors (PPARA, PPARG, PPARD) and their transcriptional coactivators' (PPARGC1A, PPARGC1B) gene polymorphisms have been associated with muscle morphology, oxygen uptake, power output and endurance performance. The purpose of this review is to determine whether the PPARs and/or their coactivators' polymorphisms can predict the training response to specific training stimuli. METHODS: In accordance with the Preferred Reporting Items for Systematic Reviews and Meta Analyses, a literature review has been run for a combination of PPARs and physical activity key words. RESULTS: All ten of the included studies were performed using aerobic training in general, sedentary or elderly populations from 21 to 75 years of age. The non-responders for aerobic training (VO₂peak increase, slow muscle fiber increase and low-density lipoprotein decrease) are the carriers of PPARGC1A rs8192678 Ser/Ser. The negative responders for aerobic training (decrease in VO₂peak) are carriers of the PPARD rs2267668 G allele. The negative responders for aerobic training (decreased glucose tolerance and insulin response) are subjects with the PPARG rs1801282 Pro/Pro genotype. The best responders to aerobic training are PPARGC1A rs8192678 Gly/Gly, PPARD rs1053049 TT, PPARD rs2267668 AA and PPARG rs1801282 Ala carriers. CONCLUSIONS: The human response for aerobic training is significantly influenced by PPARs' gene polymorphism and their coactivators, where aerobic training can negatively influence glucose metabolism and VO₂peak in some genetically-predisposed individuals.
Keywords: dospělí; kosterní svaly; transportní proteiny; Physical Conditioning, Human; Adult; jednonukleotidový polymorfismus; PPARGC1A; receptory aktivované proliferátory peroxizomů; Oxygen Consumption; lidé; Polymorphism, Single Nucleotide; Muscle, Skeletal; kondiční příprava; Peroxisome Proliferator-Activated Receptor Gamma Coactivator 1-alpha; Carrier Proteins; Male; Aged; Peroxisome Proliferator-Activated Receptors; lidé středního věku; senioři; mužské pohlaví; Middle Aged; spotřeba kyslíku; Humans